Analisis Pengaruh Pembiayaan Dan Persepsi Nasabah Terhadap Peningkatan Sektor Ekonomi Untuk Membangun System Ekonomi Yang Islami - Ferra Eka Ramadhani; Dita Rachmawati; Moh. Figo Danuarta (JURNAL INOVASI SAINS TEKNOLOGI DAN BISNIS, 2022)
One of the problems in economic development in the agricultural sector is the weak allocation of financing from formal financial institutions to the economy of the agricultural sector, which will cause a lack of capital in the sector. It is unfortunate that sharia banking, which is expected to be a financial institution that is more resistant to the crisis than conventional banking, also experiences the same thing. This article aims to express the urgency of sharia banking financing for the gross domestic product of the agricultural sector in Indonesia. In this case, the author stated that the economic growth of the agricultural sector in the short and long term is not only influenced by the demand for sharia bank financing, but that the level of capacity, effectiveness, profitability, and accessibility of sharia bank financing can also affect the economy of the agricultural sector, both in the short and long term.